An Analysis of the Communication Skills of Fifth Grade Students at SDN TAMAN - Julianti, Reka; Nurulpaik, Iik; Sopandi, Wahyu; Somantri, Mubarok; Supriatna, Encep; Bakti, Rani Citra Mutia (International Conference on Elementary Education, 2025)
Communication skills are one of the basic abilities that must be developed since elementary school because they play a crucial role in the learning process and social interactions at school. However, in reality, many elementary school students still experience difficulties in expressing ideas,expressing opinions, and actively participating in learning activities. This condition was also found at SDN Taman, Kibin District, where some students demonstrated suboptimal communication skills. This study aims to analyze the level of communication skills of fifth grade students at SDN Taman, Kibin District. The type of research used was descriptive quantitative with a sample of 52 students. The research instrument was an observation sheet based on four indicators of communication skills according to Budiono and Abdurrohman (2020), namely the ability to listen well, express ideas and thoughts effectively, convey information clearly, and provide responses to the opinions of others. The results showed that students' overall communication skills were in the sufficient category with an average score of 60%. Two indicators that achieved good results were listening and responding skills, while the other two indicators, expressing ideas and conveying information, remained in the sufficient categories. Based on these results, it is recommended that teachers implement learning models that encourage interaction, discussion, and presentation, to help students more actively express ideas and improve their overall communication skills.